EROTOMANIA AS SEEN IN PHILLIPS’ JOKER (2019) - Fadel Muhammad; Muhammad Fithratullah (Linguistics and Literature Students' Journal, 2023)
The aims of this research paper are to describe erotomania (De Clerambault’s Syndrome) as seen in the main character Arthur Fleck and its cause in the movie Joker (2019) by Todd Phillips. Here, the writer describes erotomania based on the characteristics based on Kelly’s theory (2005), which are seen in the selected scenes of the movie. Thus, in doing the research, the writer used the qualitative method. The data are taken from selected scenes from the movie and dialogues that are related to erotomania. In addition, the writer also used Metz’s semiotics of film theory (1992) in order to analyze the selected scenes that are correlated to erotomania. As a result of the findings, it indicates that the main character of Arthur Fleck in the movie Joker (2019) by Todd Phillips is possessing erotomania, or De Clerambault’s syndrome, which can be noticed from its five characteristics, namely: a delusional conviction of being in amorous communication with another person; the object is of higher rank; the sufferer believes that the object is the first to fall in love with him and the first to make advances; the object of the amorous delusions remains unchanged; and the sufferer thinks that they are not hallucinating. Moreover, the writer also found that the cause of Arthur’s erotomania is that he suffered a brain injury as a child. Keywords: erotomania, film semiotics, psychological approach